Role of Hysteroscopy in the Management of Uterine Vascular Malformations with a Focus on Enhanced Myometrial Vascularity - A Review of Diagnosis and Treatment with the Suggested Algorithm - Mohamed Siraj Shahulhameed; Bernard Su Min Chern; Ann M. Wright (Wolters Kluwer Medknow Publications, 2024)
Postpregnancy bleeding is common after failed pregnancy, termination of pregnancy, and postnatally after both vaginal and cesarean delivery. Pelvic ultrasound (US) is usually the initial imaging modality of choice to ascertain the cause when the bleeding is heavy or prolonged. When used in combination with Doppler studies, US can help differentiate retained products of conception (RPOC) from rarer uterine vascular malformations (UVM), including true arterial vascular malformations and areas of enhanced endometrial vascularity (EMV), which may themselves be associated with any RPOC present. While the management of RPOC is well established and has evolved from an almost universal surgical approach to increasingly more medical or expectant alternatives, clinical decisions over the management of a concurrent UVM are less clear and treatment options need to be individualized depending on features of the lesion and the clinical situation with hysteroscopy featured as an important modality, especially when dealing with EMV's. In this review, we discuss the role of hysteroscopy in the treatment of enhanced myometrial vascularity with and without associated RPOC and propose a management algorithm.